Cost Budget Analysis Based On Value Engineering In A 10 – Story Hotel - Damayanti, Nathania Dwi; Soleh, Muhammad Usmaidi; Nurjaman, Adam; Indah, Aryanti (Green Publisher Indonesia, 2025)
ABSTRACT The use of Value Engineering increases the value and performance of projects, with many benefits for projects and organizations, such as economical, technical, and managerial. This study discusses the application of the Value Engineering method in a 10-storey hotel construction project that aims to identify and reduce unnecessary costs without reducing the quality, function, and aesthetics of the building. The process begins with the collection of project technical data such as Detailed Engineering Design and Cost Budget Plan. Analysis was carried out on several work items, including formwork, ceiling, and façade, using the Breakdown Cost Model, FAST Diagram, and function analysis. Alternative designs are developed through creative stages, analyzed with a Life Cycle Cost approach, and evaluated in terms of advantages and disadvantages. The results show that there is a potential cost savings of IDR 533,884,167.36. The details are as follows: formwork work resulted in savings of IDR 38,713,128.61 (2.14%), ceiling work of IDR 11,518,697.38 (11.3%), and façade work of IDR 483,652,341.37 (9.14%). This research proves that the systematic application of Value Engineering can improve cost efficiency and maintain the overall quality and performance of construction.